2011
DOI: 10.1139/tcsme-2011-0026
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of a Rotary Hollow Shaft With Hot-Fit Part Using Contact Elements With Friction

Abstract: One of the key factors in designing a motor built-in high speed spindle is to assemble the motor rotor and shaft by means of hot-fit. Presented in this paper is a study of the influence of a hot-fit rotor on the local stiffness of the hollow shaft. Dynamic analyses of the rotor-hollow shaft assembly using contact elements are conducted. The normal contact stress state between the rotor and the hollow shaft is obtained through the use of contact elements with friction effects included. The normal contact stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…According to Eqs. (12), (15), and (16), the enhanced coefficient of bending stiffness can be obtained as follows:…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Eqs. (12), (15), and (16), the enhanced coefficient of bending stiffness can be obtained as follows:…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Petrescu et al [11] concluded the mass moments of inertia corresponding to different geometric shapes, objects, and profiles. Chen et al [12] studied the influence of a hot-fit rotor on the local stiffness of the hollow shaft and obtained the accurate natural frequencies using contact elements. Huang et al [13] optimized the contact stiffness factor of flexible rotor system of magnetic levitation motors and obtained the very close results of natural frequencies by ANSYS Workbench and modal experiment.…”
Section: Introductionmentioning
confidence: 99%
“…To the surface mounted high-speed PM electrical machine, the rotor assembly has different contact way between the components. The authors in [14,15] used an equivalent local elastic modulus way to simulate the local stiffness of interference fit. The contact pressure on the shaft was computed by contact theory.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 11 performed pre-stressed modal study of a hollow shaft assembly with shrink fits using Ansys. They used the native TARGE170 and CONTA174 contact elements of the software, and in order to verify the numerical results, experimental modal analysis (EMA) was performed.…”
Section: Introductionmentioning
confidence: 99%